Optimasi Penggunaan Jenis Busi, Oli, Dan Campuran Ethanol Bensin Terhadap Peningkatan Suhu Dan Jarak Tempuh Sepeda Motor 4 Langkah Dengan Metode Taguchi - Wawan Purwanto; Faris Afif; Remon Lapisa; Dori Yuvenda; M. Yasep Setiawan; Hendra Dani Saputra (Universitas Negeri Padang, 2022)
This study will look for optimal results from using the type of spark plug, oil, and gasoline ethanol mixture to increase the temperature and mileage of a 4 stroke motorcycle using the Taguchi method, which this research can also be used as a reference for further researchers. The object of research in this study is a Yamaha Vega ZR 2010 modified injection system. Data collection is done directly, such as the temperature test is carried out with an engine speed of 5000 rpm with a span of 2 minutes each run, while for the mileage test using the full to full method. Based on the results of the research that has been done, the increase in temperature gets an optimal response, namely A1 (Nickel Spark Plug) SNR response (36.2803), B3 (Shell Advance Oil) SNR response (37.8012), C2 (Ethanol gasoline 75%: 25 %) SNR response (36,4388). As for the optimal response to mileage, the factors are A2 (Iridium Spark Plug) SNR response (28.5501), B2 (Federal Racing Oil) SNR response (28.5446), C3 (Ethanol Gasoline 80%:20%) SNR response (28, 5446).